Comparison of Diagnostic Performance of Five Different Ultrasound TI-RADS Classification Guidelines for Thyroid Nodules - Yang, Ruoning; Zou, Xiuhe; Zeng, Hao; Zhao, Yunuo; Ma, Xuelei (Frontiers in Oncology, 2020)
Objectives： We aimed to evaluate and compare the diagnostic performance of five ultrasound thyroid imaging reporting and data system (TI-RADS) classification guidelines for thyroids nodules through the review and meta-analysis. Methods: We searched for relevant studies before February 2020 in PubMed. Then we pooled the sensitivity, specificity, likelihood ratios, diagnostic odds ratios, and area under the summary receiver operating characteristics curves. And the diagnostic odds ratios were used to compared the performance. Results： We totally included 19 studies with 4696 lesions in this research. The pooled sensitivity of American College of Radiology (ACR) guidelines, American Thyroid Association (ATA) guidelines, TI-RADS proposed by Kwak (Kwak TI-RADS), Korean Thyroid Association/Korean Society of Thyroid Radiology (KTA/KSThR) guidelines for malignancy risk and European Thyroid Association (ETA) guidelines is between 0.84 and 0.94. The pooled specificity is 0.68, 0.44, 0.62, 0.47and 0.61, respectively. And the RDOR is 1.57(ACR vs ATA), 1.37 (ACR vs ETA), 1.80 (ACR vs Kawk), 1.74(ARC vs KTA). Conclusions—The results suggest that five classification guidelines are all effective methods for differential diagnosis of benign and malignant thyroid nodules and ACR guideline is a better choice.